2020
DOI: 10.1002/mds.28305
|View full text |Cite
|
Sign up to set email alerts
|

TAF1 Transcripts and Neurofilament Light Chain as Biomarkers for X‐linked Dystonia‐Parkinsonism

Abstract: Background X‐linked dystonia‐parkinsonism is a rare neurological disease endemic to the Philippines. Dystonic symptoms appear in males at the mean age of 40 years and progress to parkinsonism with degenerative pathology in the striatum. A retrotransposon inserted in intron 32 of the TAF1 gene leads to alternative splicing in the region and a reduction of the full‐length mRNA transcript. Objectives The objective of this study was to discover cell‐based and biofluid‐based biomarkers for X‐linked dystonia‐parkins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 59 publications
(160 reference statements)
1
38
0
Order By: Relevance
“…An extremely skewed (98%:2%) XCI was noted in only a single case with full XDP syndrome (Domingo et al, 2014), and X-chromosome monosomy (45,X/46,XX) was found in a subset of cells of another female patient with XDP(Westenberger et al, 2013). A recent study examining the peripheral blood of 17 carrier females (4 affected with parkinsonism and 13 non affected) (Al Ali et al, 2021), is also consistent with a mosaic XCI status being protective. Decreased full length TAF1 expression, as measured by the ratio of TAF1 3’/5’, is at an intermediate level for asymptomatic carriers such that XDP patients demonstrated the most reduction and asymptomatic female carriers demonstrated intermediate reduction compared to healthy controls.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…An extremely skewed (98%:2%) XCI was noted in only a single case with full XDP syndrome (Domingo et al, 2014), and X-chromosome monosomy (45,X/46,XX) was found in a subset of cells of another female patient with XDP(Westenberger et al, 2013). A recent study examining the peripheral blood of 17 carrier females (4 affected with parkinsonism and 13 non affected) (Al Ali et al, 2021), is also consistent with a mosaic XCI status being protective. Decreased full length TAF1 expression, as measured by the ratio of TAF1 3’/5’, is at an intermediate level for asymptomatic carriers such that XDP patients demonstrated the most reduction and asymptomatic female carriers demonstrated intermediate reduction compared to healthy controls.…”
Section: Discussionmentioning
confidence: 60%
“…Canonical TAF1 expression was decreased in various XDP samples, including fibroblast, RNA from blood and NSCs, compared to control samples (Al Ali et al, 2021; Aneichyk et al, 2018; Domingo et al, 2016; Ito et al, 2016). To quantify the 3’ region of canonical TAF1 expression in XDP female carrier-derived iPSCs, we performed RT-qPCR with primers targeting TAF1 exons 32 and 33 (Rakovic et al, 2018).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Among the thirteen disease-specific variants is a ∼2.6 kb SINE-VNTR-Alu (SVA)-type retrotransposon [21] inserted in intron 32 of TAF1 [19]. XDP patient tissues and cell lines exhibit reduced TAF1 expression [19,20,2225] as well as aberrant splicing that results in partial retention of intronic sequence proximal to the SVA insertion [20]. Reduced TAF1 expression, intron retention and aberrant splicing can be rescued by excision of the SVA [20,23], suggesting that SVA-mediated TAF1 transcriptional dysregulation may contribute to disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%